PENERAPAN PENGELOLAAN SAMPAH DAN LIMBAH DI HOTEL ROYAL AVILA MALIMBU, SEBAGAI UPAYA UNTUK MEWUJUDKAN PARIWISATA BERKELANJUTAN - Cokorde Gede Bhakti Kresna; I Ketut Purwata; Indrapati Indrapati (Journal Of Responsible Tourism, 2023)
The problems studied in this study are related to environmental management at the Royal Avila Hotel Malimbu, with the aim of improving environmental management at the Royal Avila Hotel which is still not managed optimally, so that in the future sustainable tourism can be created at this hotel. The research method used is a qualitative approach. And data collection techniques in the form of interviews, observations and documentation. The results of the stdy show that the Royal Avila Hotel itself in its environmental management, especially waste and waste, is still not optimal, for waste there is no separation of organic and non-organic waste and causes a foul smell in the TPA area (final disposal site) and for the waste itself, the management is also still not optimal, the program planned by management, namely using waste water to water plants, has not been implemented, the waste water has not been managed properly in the safety tank, only filtered and then the remaining fat from the grasetrap is disposed of in the TPA. So that to assist the Management in managing its own environment, cooperation with the Waste Bank is needed to manage waste and also cooperation with companies engaged in the safety tank so that they are given medicine and knowledge to manage the waste itself, so that waste water can be used to water plants that is at the hotel. So that in the future, if the Royal Avila Hotel has implemented good environmental management, it is hoped that it will be able to create sustainable tourism in this hotel.